From Formation to Closure: Aggregate Morbidity and Mortality Associated With Defunctioning Loop Ileostomies. Issue 9 (23rd November 2021) - Yang, Mei; McClure, J. Andrew; Wanis, Kerollos N.; Vogt, Kelly N.; Van Koughnett, Julie Ann M.; Ott, Michael C.; Vinden, Christopher M.
Abstract : BACKGROUND: Defunctioning loop ileostomies are used commonly, but there are significant morbidities. OBJECTIVE: This study aimed to describe the morbidity and mortality associated with the formation and closure of defunctioning loop ileostomies. DESIGN: This descriptive study is based on electronic health records and claims data. SETTINGS: This study was conducted at academic and community hospitals in Ontario, Canada. PATIENTS: Adult patients who had a low anterior resection with concurrent defunctioning loop ileostomy from 2002 to 2014 were included. MAIN OUTCOME MEASURES: Outcomes of interest included 30-day major complications, acute kidney injury, transfusion, and deep space infection. The rate of ileostomy reversal and the percentage of permanent ostomies were also collected. RESULTS: The cohort consists of 4658 patients who underwent low anterior resection with concurrent defunctioning loop ileostomy. The 30-day, 90-day, and 1-year mortality rates of these patients were 1.2%, 2.2%, and 5.1%. The rate of reoperation was 5.5%, the rate of hospital readmission was 13.4%, the rate of major complications was 28.5%, the rate of deep organ/space infection requiring percutaneous intervention was 5.2%, and the rate of acute kidney injury requiring hospitalization was 10.4%. Eighty-six percent had their ileostomy reversed, leaving 13.2% with a permanent ostomy. After ileostomy reversal, 30-day and 90-day mortality rates were 0.6% and 0.9%. The rate of major complications was 10.3%, bowel obstruction 7%, ventral hernia 10.5%, deep space infection 1.7%, and repeat operation 2.3%. LIMITATIONS: This study is based on electronic health records and claims data and, thus, the accuracy of results depends on the accuracy of data administration‚ which can be variable across institutions. CONCLUSIONS: Morbidity and mortality of defunctioning loop ileostomies are significant. One in 8 patients will have a permanent ostomy. See Video Abstract at http://links.lww.com/DCR/B810 . DESDE LA FORMACIÓN HASTA EL CIERRE: AGREGADA MORBILIDAD Y MORTALIDAD ASOCIADA CON LAS ILEOSTOMÍAS EN ASA DERIVATIVA: ANTECEDENTES: Las ileostomías en asa derivativa se utilizan con frecuencia, pero existen morbilidades importantes. OBJETIVO: Describir la morbilidad y mortalidad asociadas con la formación y cierre de ileostomías en asa derivativa. DISEÑO: Estudio descriptivo basado en historias clínicas electrónicas y datos de reclamaciones. ENTORNO CLINICO: Hospitales académicos y comunitarios en Ontario, Canadá. PACIENTES: Pacientes adultos sometidos a resección anterior baja con concurrente ileostomía en asa derivativa de 2002 a 2014. PRINCIPALES MEDIDAS DE VALORACION: Los resultados de interés incluyeron complicaciones mayores a los 30 días, lesión renal aguda, transfusión e infección del espacio profundo. También se recolectó la tasa de reversión de la ileostomía y el porcentaje de ostomías permanentes. RESULTADOS: La cohorte consistió de 4658 pacientes sometidos a resección anterior baja con concurrente ileostomía en asa derivativa. La mortalidad de estos pacientes, a treinta días, 90 días y un año, fue del 1, 2%, 2, 2% y 5, 1%, respectivamente. La tasa de reintervención fue del 5, 5%, el reingreso hospitalario fue del 13, 4%, la complicación mayor fue del 28, 5%, la infección profunda de órganos / espacios que requirieron intervención percutánea fue del 5, 2%, y la lesión renal aguda que requirió hospitalización fue del 10, 4%. Ochenta y seis por ciento tuvieron reversión de su ileostomía, dejando al 13.2% con una ostomía permanente. Después de la reversión de la ileostomía, la mortalidad a los 30 días y 90 días fue de 0, 6% y 0, 9%, respectivamente. La tasa de complicaciones mayores fue del 10, 3%, obstrucción intestinal del 7%, hernia ventral del 10, 5%, infección del espacio profundo del 1, 7% y reintervención del 2, 3%. LIMITACIONES: El estudio se basa en registros médicos electrónicos y datos de reclamos y, por lo tanto, la precisión de los resultados depende de la precisión en la administración de datos, que pueden variar entre instituciones. CONCLUSIONES: La morbilidad y la mortalidad de las ileostomías en asa derivativa son significativas. Uno de cada 8 pacientes tendrá una ostomía permanente. Consulte Video Resumen en http://links.lww.com/DCR/B810 . (Traducción—Dr. Fidel Ruiz Healy )